The Effects of Temperature and Environmental Carbon dioxide to Reef Fish Condition - Zaky Alin Nuary (Jurnal Perikanan dan Kelautan, 2020)
The dynamics of climate conditions occur as a result of national development to have an impact on the condition of the atmosphere and ocean environment. This condition causes a change of coral reef fish live, as much as 50% of reef fishes die when extreme temperatures occur in Australia. Research related to changes in temperature and carbon dioxide conditions becomes very important to see changes in coral reef fish conditions. Several previous studies about impact of climate change to coral reef fish used many species of coral reef fishes in different location have shown a significant change in morphology, genetic, and behavior of reef fishes when there are changes in environmental conditions. Morphological results showed a decrease in length and weight of coral reef fish; genetic result showed an upregulated and downregulated function of genetic in coral reef fish.